Neuromuscular fatigue and time motion analysis during a table tennis competition - Mansec, Y.; Seve, C.; Jubeau, M. (The Journal of Sports Medicine and Physical Fitness, 2017)
BACKGROUND: This study aimed to determine the neuromuscular fatigue (central versus peripheral mechanisms) as well as the game characteristics and physical demand induced by a simulated table tennis competition.